Strategi Penguatan Ecopreneurship pada UMKM Fashion Berkelanjutan (Studi Kasus Aeleen Ecoprint Malang) - Didit Jefry Andyanto; Galih Putra Riatma; Yoan Santosa Putra; Affan Afian (Universitas Madako Tolitoli, 2026)
This study analyzes the implementation of the ecopreneurship concept at Aeleen Ecoprint MSME in Malang, identifies internal and external factors influencing business development, examines various constraints faced, and formulates ecopreneurship strengthening strategies to enhance business competitiveness and sustainability. Using a qualitative approach with a case study design, data were collected through participatory observation, in-depth interviews, documentation, and a literature review. The data were then analyzed using the Miles, Huberman, and Saldana interactive model combined with a SWOT analysis. The findings indicate that Aeleen Ecoprint has successfully applied ecopreneurship principles by using natural raw materials, adopting zero-waste waste management practices, and developing eco-friendly sustainable fashion products that deliver economic value. Nevertheless, the business still faces challenges, including production capacity limitations, sub-optimal digital marketing, and market competition. To address these issues, the recommended strengthening strategies comprise product innovation, digital transformation, human resource competency enhancement, and multi-stakeholder collaboration to foster sustainable business growth.